The Influence of the Crops Upon Business in America - Andrew, A. Piatt (Quarterly Journal of Economics, 1906)
The Influence of the Crops upon Business in America Get access A. Piatt Andrew A. Piatt Andrew Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 3, May 1906, Pages 323–352, https://doi.org/10.2307/1882854 Published: 01 May 1906